The role of mesenchymal G proteins in pulmonary fibrosis and lung development - Goodwin, Amanda T. (2021)
The maintenance of lung homeostasis is complex and involves the concerted actions of numerous cell types and signalling pathways. Any disturbance to these intricate processes and interactions can result in lung disease, such as pulmonary fibrosis. In pulmonary fibrosis, an abnormal wound healing response involving the abnormal recapitulation of developmental signalling pathways occurs, resulting in scarring of the lungs. An understanding of normal lung developmental pathways, and how they become abnormally reactivated in pulmonary fibrosis, may hold the key to creating regenerative strategies to benefit patients with this condition.